"حركة نیاغارا" في الولایات المتحدة الامریكیة: مقدماتھا ، نشأتھا، ١٩١٠- وعوامل انھیارھا ١٨٩ - أ.م.د.كریم صبح عطیة (College of Education for Women, 2019)
The Negro minority in the United States is associated with social injustice, political deprivation, and economic oppresion. Its members felt that they are second-class citizens, and that the acceptance of such status will lead to the continual oppresion of the Whites upon them. As a result, the educated community adopted a process to put a framework to their opposition to the former's injustice. This organised framework is exemplified in the "Niagara Movement," which is regarded as the first national organisation for Negros. The topic of this study is chosen due to its historical and political significance. The study consists of an introduction and five sections. The first section addresses the preliminaries and the factors of the Movement establishment. It also deals with the conditions of the Blacks, and the emergence of some of the leaders among them, whether those who made negotiations with the Whites, or those who rejected the bad conditions of the Blacks and sought to change them through establishing the Movement. The second section studies the Movement establishment conference, and the objectives to be achieved. While the third section examines the Movement numerous activities and the most important factors of its vulnerability. The fourth section includes the subjective and objective factors that led to the the Movement collapse . The final section contains an assessment to the Movement that shows its pros and cons according to the analytical historical method of research.